Standardizing definitions and reporting guidelines for the infertility core outcome set: an international consensus development study . Issue 12 (30th November 2020) - Duffy, J M N; Bhattacharya, S; Bhattacharya, S; Bofill, M; Collura, B; Curtis, C; Evers, J L H; Giudice, L C; Farquharson, R G; Franik, S; Hickey, M; Hull, M L; et al.
Abstract: STUDY QUESTION: Can consensus definitions for the core outcome set for infertility be identified in order to recommend a standardized approach to reporting? SUMMARY ANSWER: Consensus definitions for individual core outcomes, contextual statements and a standardized reporting table have been developed. WHAT IS KNOWN ALREADY: Different definitions exist for individual core outcomes for infertility. This variation increases the opportunities for researchers to engage with selective outcome reporting, which undermines secondary research and compromises clinical practice guideline development. STUDY DESIGN, SIZE, DURATION: Potential definitions were identified by a systematic review of definition development initiatives and clinical practice guidelines and by reviewing Cochrane Gynaecology and Fertility Group guidelines. These definitions were discussed in a face-to-face consensus development meeting, which agreed consensus definitions. A standardized approach to reporting was also developed as part of the process. PARTICIPANTS/MATERIALS, SETTING, METHODS: Healthcare professionals, researchers and people with fertility problems were brought together in an open and transparent process using formal consensus development methods. MAIN RESULTS AND THE ROLE OF CHANCE: Forty-four potential definitions were inventoried across four definition development initiatives, including the Harbin Consensus Conference Workshop Group and International Committee for Monitoring Assisted Reproductive Technologies, 12 clinical practice guidelines and Cochrane Gynaecology and Fertility Group guidelines. Twenty-seven participants, from 11 countries, contributed to the consensus development meeting. Consensus definitions were successfully developed for all core outcomes. Specific recommendations were made to improve reporting. LIMITATIONS, REASONS FOR CAUTION: We used consensus development methods, which have inherent limitations. There was limited representation from low- and middle-income countries. WIDER IMPLICATIONS OF THE FINDINGS: A minimum data set should assist researchers in populating protocols, case report forms and other data collection tools. The generic reporting table should provide clear guidance to researchers and improve the reporting of their results within journal publications and conference presentations. Research funding bodies, the Standard Protocol Items: Recommendations for Interventional Trials statement, and over 80 specialty journals have committed to implementing this core outcome set. STUDY FUNDING/COMPETING INTEREST(S): This research was funded by the Catalyst Fund, Royal Society of New Zealand, Auckland Medical Research Fund and Maurice and Phyllis Paykel Trust. Siladitya Bhattacharya reports being the Editor-in-Chief of Human Reproduction Open and an editor of the Cochrane Gynaecology and Fertility Group. J.L.H.E. reports being the Editor Emeritus of Human Reproduction . R.S.L. reports consultancy fees from Abbvie, Bayer, Ferring, Fractyl, Insud Pharma and Kindex and research sponsorship from Guerbet and Hass Avocado Board. B.W.M. reports consultancy fees from Guerbet, iGenomix, Merck, Merck KGaA and ObsEva. C.N. reports being the Editor-in-Chief of Fertility and Sterility and Section Editor of the Journal of Urology, research sponsorship from Ferring, and a financial interest in NexHand. E.H.Y.N. reports research sponsorship from Merck. A.S. reports consultancy fees from Guerbet. J.W. reports being a statistical editor for the Cochrane Gynaecology and Fertility Group. A.V. reports that he is a Statistical Editor of the Cochrane Gynaecology & Fertility Review Group and of the journal Reproduction . His employing institution has received payment from Human Fertilisation and Embryology Authority for his advice on review of research evidence to inform their 'traffic light' system for infertility treatment 'add-ons'. N.L.V. reports consultancy and conference fees from Ferring, Merck and Merck Sharp and Dohme. The remaining authors declare no competing interests in relation to the work presented. All authors have completed the disclosure form. TRIAL REGISTRATION NUMBER: Core Outcome Measures in Effectiveness Trials Initiative: 1023.